Removal efficacy and cytotoxicity of a calcium hydroxide paste using N-2-methyl-pyrrolidone as a vehicle - Myung-Jin Lim; Hyun-Jin Jang; Mi-Kyung Yu; Kwang-Won Lee; kyung-San Min (Korean Academy of Conservative Dentistry, 2017)
Objectives This study investigated the removal efficacy and cytotoxicity of a newly developed calcium hydroxide paste (cleaniCal, Maruchi) using N-2-methyl-pyrrolidone (NMP) as a vehicle in comparison with ApexCal (Ivoclar Vivadent) and Calcipex II (Nishika), which use different vehicles such as polyethylene glycol and propylene glycol, respectively. Materials and Methods Thirty maxillary premolars with oval-shaped canals were divided into 3 groups and the teeth were filled with one of the pastes. After removal of the paste, micro-computed tomographic (μ-CT) imaging was obtained to assess the volume of residual paste in the root canal of each tooth. The teeth were then split longitudinally and the area of the paste-coated surface was evaluated by stereomicroscopy. The cytotoxicity of each product was assessed using an agar overlay assay. The effect of each vehicle on cell viability was evaluated using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The data were analyzed using one-way analysis of variance and Tukey's tests to detect any significance (p < 0.05). Results In the μ-CT and stereomicroscopic analysis, cleaniCal exhibited less remnants of medicament than ApexCal and Calcipex. cleaniCal showed a higher cytotoxicity than the other pastes in the agar overlay assay. Furthermore, NMP exhibited lower cell viability compared to the other vehicles. Conclusions cleaniCal showed better removal efficacy compared to the other products. However, clinicians should be aware of the higher cytotoxicity of the NMP-based material and consider its possible adverse effects on periradicular tissue when it is overfilled.